Investigating the Effects of Pre-Competition Anxiety on Sport Psychological Performance in Young Athletes Performance - Aulya Safiyna Nuuril Anwari; Nura Maulida Isna; Muhammad Reza Aziz Prasetya; Achmad Widodo; Anung Priambodo (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
Introduction: success in competition is influenced by various factors including emotion management skills and psychological conditions before competition. pre-competition anxiety is a condition that is widely experienced in adolescent athletes, especially in athletes who are new to competing in elite competitions. this study was conducted to look further at anxiety levels, influencing factors and the effect of pre-competition anxiety on match performance in achieving achievement. Methods: this systematic review protocol adheres to the PRISMA 2020 guidelines. A systematic search was conducted using the popular databases Scopus, ScienceDirect and PubMed published between 2020 and 2025. The search was conducted on peer reviewed articles written in English, and reported on the condition of pre-competition anxiety on competition performance in young athletes aged 12-18 years who competed in professional events. Result: Of the total 975 publications initially identified, 9 studies met the selection criteria for inclusion in this review. These articles explored the effects of pre-competition anxiety on sports performance across various athletic disciplines. The studies provided insights into varying levels of pre-competition anxiety, different interventions aimed at reducing anxiety, and their subsequent effects on performance outcomes. The findings suggest that pre-competition anxiety can significantly impact performance, with both positive and negative effects depending on the anxiety level and intervention methods employed.